Pengunaan Pasir dan Kerikil dalam Memenuhi Kebutuhan dan Dampaknya Terhadap Lingkungan Hidup Masyarakat di Desa Nusarua Kecamatan Fena-Fafan. Kabupaten Buru Selatan - Celsya Puturuhu; Melianus Salakory; Dwi Partini (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2025)
The availability of natural resources such as sand and gravel plays a crucial role in supporting rural infrastructure development. However, their use often raises a dilemma between construction needs and environmental sustainability. This study aims to describe the utilization process of sand and gravel in Nusarua Village, Fena-Fafan District, South Buru Regency, and to examine its impact on the community’s social life and environment. A qualitative field research method was applied, involving observation, interviews, and documentation with both mining participants and affected villagers. The findings indicate that sand and gravel extraction provides significant economic benefits by increasing household income and supplying essential materials for housing and village infrastructure. On the other hand, it causes negative impacts such as environmental degradation, landslide risks, vegetation loss, and threats to community safety. These results highlight the necessity for wiser natural resource management through village government oversight and community awareness. The study recommends adopting sustainable utilization strategies so that development can continue without sacrificing environmental balance